THE EFFECT OF THE DIAMETER OF THE PILING ROLLER OF THE POMEGRANATE BURYING MACHINE ON ITS PERFORMANCE INDICATORS - Abdunazarov Elbek Elmurodovich; Khamzaeva Shakhlo Muminovna (Modern American Journals, 2025)
This article presents the results of research on the operational parameters of a pomegranate burying machine, focusing on the effect of the piling roller's diameter on its performance indicators. Experiments were conducted by varying the small and large diameters of the piling rollers across different intervals under operating speeds of 5 km/h and 7 km/h. The study analyzed the cutting, breaking, and tearing rates of the pomegranate bush trunk part, as well as the damage rate of pomegranate branches. The results demonstrated that increasing the large diameter of the rollers from 30 mm to 70 mm significantly reduced the damage rates, while further increases had a negligible effect. The optimal small and large diameters of the rollers were determined to be 55 mm and 70 mm, respectively, ensuring compliance with agrotechnical requirements. The findings provide valuable insights into improving the machine's design to minimize crop damage and enhance efficiency in pomegranate burying operations.
Keywords: Pomegranate burying machine, piling roller, cutting rate, breaking rate, tearing rate, damage rate, agrotechnical requirements.